2020
DOI: 10.3390/rs12030431
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation and Minimum Temperature are Primary Climatic Controls of Alpine Grassland Autumn Phenology on the Qinghai-Tibet Plateau

Abstract: Autumn phenology is a crucial indicator for identifying the alpine grassland growing season’s end date on the Qinghai-Tibet Plateau (QTP), which intensely controls biogeochemical cycles in this ecosystem. Although autumn phenology is thought to be mainly influenced by the preseason temperature, precipitation, and insolation in alpine grasslands, the relative contributions of these climatic factors on the QTP remain uncertain. To quantify the impacts of climatic factors on autumn phenology, we built stepwise li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…It is possible that rather than air temperature, leaf temperature could be a better predictor of leaf senescence (Liu et al, 2020). Wu et al (2018) also revealed a contrasting effect of daytime and nighttime warming on autumn leaf senescence of plants in the Northern Hemisphere using ground phenological records and satellite greenness data, indicating a more complex response of plant autumn phenology to thermal conditions than presented in existing phenological models (An et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is possible that rather than air temperature, leaf temperature could be a better predictor of leaf senescence (Liu et al, 2020). Wu et al (2018) also revealed a contrasting effect of daytime and nighttime warming on autumn leaf senescence of plants in the Northern Hemisphere using ground phenological records and satellite greenness data, indicating a more complex response of plant autumn phenology to thermal conditions than presented in existing phenological models (An et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, it was unlikely that model parameters calibrated on the basis of any single site could be utilized consistently at other sites (Table 3), suggesting that site‐specific model calibrations are not reliable for spatial extrapolation (Botta, Viovy, Ciais, Friedlingstein, & Monfray, 2000; Tao et al, 2018). For predicting regional phenology, it is essential to build spatially independent models for all sites covering the entire region, which is, however, technically inefficient (An et al, 2020). Going forward, a way to obtain better predictions at the regional scale is to establish a generalized model over the whole region that is driven by both climatic and genotypic factors (Liang, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Alpine meadow, as the dominant ecosystem on the QTP, is highly sensitive to ). An et al (2020) found the daily minimum air temperature can be a key factor for controlling autumn phenology in alpine grasslands, which a 1°C increase in the mean autumn minimum temperature during the optimum length period may induce a delay of 1.6 to 9.3 days in the middle senescence date across the alpine grasslands.…”
Section: Variations In Sfpmentioning
confidence: 96%
“…Higher preseason precipitation could also alter spring phenology ( Dai et al, 2013 ; Piao et al, 2019 ; Zhou et al, 2019 ), because more precipitation may increase the heat demand of spring phenology ( Fu et al, 2014 ). Photoperiod may also influence bud burst, but generally in a minor way ( Chen et al, 2017 ; An et al, 2020 ). To date, the mechanisms by which photoperiod affects phenology remain unexplored experimentally ( Liu et al, 2016a ).…”
Section: Introductionmentioning
confidence: 99%